2017
DOI: 10.1111/joic.12366
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention of Complex Calcified Lesions With Drug‐Coated Balloon After Rotational Atherectomy

Abstract: This is the first study to show that PCI using DCB after preparation of calcified lesions with rotablation is safe and effective. This novel strategy may be considered especially in patients with a bleeding risk such as those using an oral anticoagulant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 35 publications
(92 reference statements)
2
32
1
Order By: Relevance
“…To date, DCB has been approved for the treatment of in‐stent restenosis by the guidelines but there are many other emerging indications such as small vessels, bifurcations, diffuse disease, chronic total occlusions and calcified complex lesions . Data on the performance of DCB in de novo lesions of large coronaries have previously been scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, DCB has been approved for the treatment of in‐stent restenosis by the guidelines but there are many other emerging indications such as small vessels, bifurcations, diffuse disease, chronic total occlusions and calcified complex lesions . Data on the performance of DCB in de novo lesions of large coronaries have previously been scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The 606 PCIs with paclitaxel‐coated DCB encompassing iopromide as a carrier agent (SeQuent Please, B. Braun) were performed between September 2009 and December 2013 in our institution. The only exclusion criteria for the current study were rotational atherectomy ( n = 82, published elsewhere) and in‐stent restenosis ( n = 37). Thus, the study cohort consisted of 487 PCIs done using DCB during this time period (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that 19% of patients with ACS were successfully treated using ELCA alone without stenting. Another study showed that favorable outcomes were achieved by DCB applications following rotational atherectomy for calcified lesions without the help of stent deployment. Inspired by those studies, we proposed a novel approach with the use of a combination of the two aforementioned stent‐free devices.…”
Section: Introductionmentioning
confidence: 99%
“…Planned RA resulted in less contrast use, fluoroscopy time, fewer dissections, higher angiographic success, and reduced in‐hospital MACE. Similarly, Rissanen et al reported 82 heavily calcified lesions treated with RA followed by drug coated balloon (DCB) with excellent success and low bail out stenting (10%), TLR at 12 (1.5%) and 24 months (3.0%).…”
Section: Calcified Coronariesmentioning
confidence: 95%